Mulheres lutando contra o HIV/SIDA: cuidadoras de Moçambique - Casimiro, Isabel Maria; Fauré, Yves-A; Tembe, Carlota Mondlane; Mutisse, Luisa Chicamisse (Desafios para Moçambique 2022, 2022)
Moçambique é um país caracterizado por índices elevados de pobreza onde a prevalência do Vírus da Imunodeficiência Humana (HIV)/Síndrome da Imunodeficiência Adquirida (SIDA) é muito alta e a taxa de incidência ainda preocupante, e cujos meios de combate à doença são limitados e dependem, em parte, da ajuda externa. A súbita emergência e rápida expansão da covid-19, a partir do início de 2020, teve um impacto negativo nas condições de tratamento das PVHIV, que, de certa forma, sofreram uma dupla aflição. Os serviços de saúde essenciais foram afectados - prevenção, diagnóstico, tratamento, cuidados paliativos e reabilitativos, etc. - com efeitos graves nos doentes mais vulneráveis (crianças, idosos, pessoas que vivem com doenças crónicas). Com este estudo, pretendemos apresentar os resultados obtidos através da divulgação das iniciativas das mulheres junto às autoridades públicas, instituições nacionais e internacionais, agências de cooperação bilaterais, associações e ONGs moçambicanas e estrangeiras dedicadas de uma ou de outra forma à luta contra o HIV/SIDA. Finalmente, almejamos examinar as condições em que estas iniciativas poderiam ser integradas ou pelo menos aproximadas das Unidades Sanitárias que trabalham na área do HIV/SIDA.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; gender / género; health / saúde; society / sociedade

A questão do género sob uma perspectiva histórica, nas políticas de saúde em Moçambique - Rosário, Carmeliza (Desafios para Moçambique 2022, 2022)
O presente capítulo é baseado numa revisão histórica das políticas sociais desenvolvidas em Moçambique. Dentre as políticas sociais do País, a saúde tem sido consistentemente um dos sectores privilegiados. Já durante o tempo colonial, apesar das políticas discriminatórias entre a população indígena e a colonial, a saúde sempre figurou como preocupação governativa, particularmente em benefício das populações trabalhadoras assalariadas, em detrimento das não assalariadas. Além disso, os aspectos discriminatórios estendiam-se também à priorização dos homens como força laboral e à visão das mulheres e crianças como dependentes, criando inclusivamente benefícios maiores para homens casados e cimentando a perspectiva do homem como provedor. Na análise que se segue, apresenta-se o percurso legislativo do sector de saúde e os ideais preconizados nesta legislação, com particular atenção para a mulher e a sua consideração na mesma. De seguida, apresenta-se a desconexão estrutural que se tem verificado, em relação aos ideais preconizados. Por fim, apresentam-se exemplos sobre como as políticas de outros sectores podem afectar o sector da saúde e produzir efeitos transformadores incluindo de impacto para a equidade de género. Para tal, argumenta-se que, pese embora os desafios que o País enfrenta, de crises recorrentes, falta de recursos e dependência pela ajuda externa, é necessário determinar o tipo de Estado que se quer, social ou mercantilista. Deve ainda ultrapassar-se a visão limitada da saúde da mulher relacionada com sexualidade e reprodução e do papel do homem na saúde como condutor ou repressor dessas funções da mulher.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; gender / género; society / sociedade

Classes of working women in Mozambique: an integrated framework to understand working lives - Stevano, Sara (Review of International Political Economy, 2022)
Feminist political economy has illuminated the gendered dimensions of the globalisation of production. Whilst this literature provides essential insights on gendered exploitation in export-oriented industries, women’s work in localised labour markets in the Global South remains underexplored. This paper seeks to address this gap by putting into dialogue three bodies of literature – feminist political economy of globalisation, political economy of development in southern Africa and the social reproduction of the everyday. It proposes an integrated conceptual framework to analyse women’s working lives and applies it to northern Mozambique. It makes two key findings. First, the lives of those working in localised labour markets are shaped by global capitalism through extreme fragmentation of labour regimes forcing people into multiple precarious forms of work – a process that entails the appropriation of women’s productive and reproductive labour. Second, the imperatives of social reproduction shape employment trajectories and expose differentiation among working women, seen for example through gendered constraints to mobility, care obligations and contributions to ceremonies. The implications are that the analysis of women’s working lives needs to capture three key aspects: social differentiation among working women, temporal and spatial dynamics of the everyday and the centrality of the reproduction of the social.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; gender / género; labour regimes / regimes de trabalho; social protection / proteção social; social reproduction / reprodução social

The Role of Women in the Conflict in Cabo Delgado: Understanding Vicious Cycles of Violence - Feijó, João (Observatório do Meio Rural, 2021)
Since October 2017, Cabo Delgado Province has been an arena of armed conflict, translating into destruction and looting, abductions and killings of civilian populations. The conflict intensified throughout 2020, with attacks on district headquarters villages, leading to the forced displacement of hundreds of thousands of individuals. The history of armed conflicts in Mozambique shows that they have had enormous impacts on the civilian population, placed between two opposing groups: rebel forces and government forces. Aware of their respective importance in a guerrilla war (for the possibility of logistical support, camouflage, recruitment, or the provision of information), the warring parties have always related to the civilian population on the basis of mistrust, imposing their domination by force and persuasion, and seeking to interfere in their habitat (in clusters or scattered in the bush). Being physically more fragile, target for sexual predation by armed young men, and traditionally a food producer, women were a recurrent target, remaining in a particularly vulnerable position. In the current armed conflict in northeast Cabo Delgado, there have been numerous reports of abduction of hundreds of young women, and there is much doubt about their whereabouts. However, viewing women only as passive victims of the conflict does not capture the complexity of the situation. Voluntarily or forcibly, by conviction or without choice, the literature shows that women play an active role in armed conflicts, as observers and providers of military information, in providing logistical support, as vigilantes, and even as soldiers. This active involvement of women is all the more evident the larger the social support base of the insurgent groups. This study aims to portray the impact of the armed conflict on women during the armed conflict in northern Cabo Delgado, analyzing not only the wide range of violence committed against them, but also the forms of collaboration (more or less voluntary) with rebel groups and their organizational dynamics.
ISBN: 978-2-490093-28-1
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; gender / género; ⛔ No DOI found

Caracterização e Organização Social Dos Machababos a Partir dos Discursos de Mulheres Raptadas - Feijó, João (Observatório do Meio Rural, 2021)
A intensificação do conflito militar no Norte de Cabo Delgado despertou a atenção de jornalistas, investigadores, analistas de segurança e diplomatas. O facto de os rebeldes armados não darem entrevistas a jornalistas e investigadores resulta num grande desconhecimento sobre as suas dinâmicas internas nas zonas ocupadas, pelo que o mundo dos insurgentes constitui um território repleto de mistérios. Por outro lado, o rapto de centenas de jovens mulheres gera interrogações em torno do respectivo paradeiro, originando inquietação social. O pouco conhecimento existente acerca das formas de organização interna dos insurgentes resulta de testemunhos oculares de quem privou com o grupo, nomeadamente desertores ou mulheres que estiveram em cativeiro. A partir de 23 entrevistas a mulheres vítimas de agressão ou sequestro por grupos insurgentes foi possível concluir que os membros do grupo têm origens e percursos sociogeográficos heterogéneos, sendo a maioria oriunda do litoral Norte de Cabo Delgado, com registos de indivíduos provenientes do planalto de Mueda, do litoral de Nampula, assim como um crescente número de estrangeiros, provenientes da costa oriental africana e de países árabes. Os insurgentes dispõem de diferentes bases, instaladas em aldeias abandonadas por civis ou nas matas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Characterization and Social Organization of Machababos from the Discourses of Kidnapped Women - Feijó, João (Observatório do Meio Rural, 2021)
The intensification of the military conflict in Northern Cabo Delgado has attracted the attention of journalists, investigators, security analysts and diplomats. The fact that armed rebels do not give interviews to journalists and researchers results in a great ignorance about their internal dynamics in the occupied areas, and so the world of insurgents is a territory full of mysteries. On the other hand, the abduction of hundreds of young women raises questions about their whereabouts, causing social unrest. The little knowledge of the insurgents' forms of internal organization stems from eyewitness testimonies of those who lived with the group, including defectors or women who have been in captivity.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Strengthening Women’s Inclusion in Social Accountability Initiatives - Nazneen, Sohela; Silva Olivares, Maria Fernanda (2021)
In the last 20 years, social accountability initiatives have facilitated the inclusion and participation of marginalised groups in governance processes. This Policy Briefing focuses on how and what factors prove effective in strengthening women’s voice in processes holding public service providers accountable. We argue that initiatives must: (a) build technical and other forms of capacity amongst women; (b) change formal rules on women’s inclusion; (c) apply political economy analysis to unpack power dynamics, identify actors in favour of gender equality, and build a network in support of women; and (d) make long-term funding commitments for sustainable change in gender-biased norms.
Accepted: 2021-02-18T10:37:09Z Publisher: Institute of Development Studies
Keywords: *tagged; L - english / inglês; accountability / responsabilização; gender / género; social inclusion & exclusion / inclusão e exclusão social

Shaping Social Change with Music in Maputo, Mozambique - Taela, Kátia; Gonçalves, Euclides; Maivasse, Catija; Manhiça, Anésio (IDS, 2021)
In Mozambique, development programmes have traditionally drawn on music as a means to promote social transformation by educating citizens on key social development issues. Shifting the focus from music as a teaching medium to music as a rich source of information can provide vital insights into public opinion and political ideas, and significantly impact the development of citizen engagement projects. Maximum gains for development and civil society agencies can be achieved by mainstreaming gender into mutual learning activities between singers, audiences, and academics.
Keywords: *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; empowerment / empoderamento; gender / género

Estimating the cost of implementing a facility and community score card for maternal and newborn care service delivery in a rural district in Uganda - Ssebagereka, Anthony; Apolot, Rebecca Racheal; Nyachwo, Evelyne Baelvina; Ekirapa-Kiracho, Elizabeth (International Journal for Equity in Health, 2021)
This paper aimed at estimating the resources required to implement a community Score Card by a typical rural district health team in Uganda, as a mechanism for fostering accountability, utilization and quality of maternal and child healthcare service.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; community scorecard (CSC) / cartão de pontuação comunitária (CPC); gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Relatório de Pesquisa Desigualdades e Resistência em Tempos de Pandemia: Impactos Da COVID-19 Nas Mulheres do Mercado Informal - Osório, Conceição; Loforte, Ana Maria; Vilanculo, Sérgio (WLSA Moçambique, 2021)
Este relatório de pesquisa buscou especificamente identificar no contexto mundial, regional e nacional as estratégias e as políticas públicas relativamente à situação das raparigas e mulheres, analisar as narrativas e discursos das organizações da sociedade civil e instituições de pesquisa, tanto as que têm como foco os direitos humanos, como as que definem como objecto a promoção da igualdade de género, e analisar o conteúdo dos media nacionais sobre a Covid-19, com destaque para as representações sobre violência de género. Para a realização da pesquisa foi importante a definição do grupo alvo, as mulheres que trabalham no informal, por serem das mais afectadas pela situação criada pela Covid-19, sendo muito pouco conhecidas as suas vozes, os seus problemas, necessidades e expectativas. A pesquisa foi enquadrada no Projecto “Mulheres e direitos humanos no contexto da COVID-19 em Moçambique” e surgiu no âmbito de uma parceria entre a WLSA Moçambique com as Aliadas e o CESC, procurando conhecer melhor como é que, em situação de pandemia, se configuravam os direitos humanos das mulheres, considerando as desigualdades estruturais e as relações desiguais de poder.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; informality / informalidade

Innovative Finance for Employment: The Potential for Women and Urban Youth - MUVA; Social Finance Ltd (MUVA and Social Finance Ltd, 2021)
The need for female economic empowerment in Mozambique is clear; just 24% of women have access to wage employment, versus 50% of men. The situation is worse still in urban settings where 19-24-year-old women have the highest unemployment rates in the country. The national rate of formal employment is approximately 13%, and large scale formal job creation in the Oil and Gas sector is yet to materialise. Despite impressive economic growth in recent years, 50% of Mozambicans are still living in poverty and social and economic inequalities are continuing to grow. The challenges faced by disadvantaged urban youth and women (DUYW) are severe; without deliberate intervention to address the constraints facing them, this trend is set to worsen. In light of this challenge, MUVA commissioned a scoping study to assess the potential of innovative financing models to support the economic empowerment of disadvantaged urban youth and women. Innovative finance is a broad spectrum of mechanisms that offer an alternative to traditional activity based grant funding. It can include investment capital seeking a return, but also encompasses results based financing and broader risk mitigation mechanisms. If done correctly, innovative finance can support good interventions to better tackle entrenched social issues, by sharpening incentives, creating accountability for results, addressing specific barriers in the system, shifting where risk is held and fostering adaptive management. The study identified four innovative financing models that have the potential to enable disadvantaged urban youth and women in Mozambique to access economic opportunities. Some focus more on the supply side, working primarily with DUYW to improve their skills, employability and facilitate entry into the workforce. Others focus on the demand side, working with enterprises to enable them to scale, improve gender practices and encourage them to employ DUYW. Two of the shortlisted models sit across both demand and supply.
Keywords: G - Mozambique / Moçambique; L - english / inglês; employment / emprego; empowerment / empoderamento; gender / género; private sector / setor privado; urbanization / urbanização; youth / juventude

Qualidade da assistência pré-natal em Nampula, Moçambique - Muleva, Belarmina Reis (Universidade de São Paulo, 2020)
A realização da consulta pré-natal de alta qualidade está diretamente relacionada aos melhores indicadores maternos e fetais e à prevenção de morbimortalidade materna. Em Moçambique, estudos sobre assistência pré-natal mostram que a maior parte das mulheres fez pré-natal, mas apenas metade fez as quatro ou mais consultas preconizadas pelo Ministério da Saúde. Além disso, as gestantes têm se apresentado aos centros de saúde para fazerem sua primeira consulta pré-natal somente no final do segundo trimestre da gestação. Essas questões mostram que a qualidade da assistência ao pré-natal é ainda um desafio, embora haja poucos estudos sobre o tema naquele contexto. Objetivo: Avaliar a qualidade da assistência pré-natal entre as mulheres do município de Nampula, em Moçambique. Método: Trata-se de um estudo quantitativo, do tipo transversal, realizado no município de Nampula, em Moçambique, na África. A amostra constou de 393 mulheres de 18 a 49 anos, com parto ocorrido em maternidade ou no domicílio no segundo semestre de 2019. As entrevistas foram conduzidas por meio de instrumento estruturado, aplicado face-a-face, até 15 dias após o parto. A qualidade da assistência pré-natal foi analisada com base nas diretrizes do Ministério da Saúde de Moçambique. A qualidade do pré-natal foi categorizada em inadequada e adequada. Modelos de regressão logística múltipla foram conduzidos para analisar os aspectos associados a ter realizado pré-natal adequado. Resultados: As mulheres participantes do estudo tinham, em média, 26 anos de idade, e metade tinha ensino primário (52,4%). Embora todas as mulheres tenham realizado o pré-natal, apenas 13,0% tiveram o pré-natal classificado como adequado. Mulheres que realizaram pré-natal em gestações anteriores (OR=4,28; IC95%=1,45-12,62) e com gravidez planejada (OR=2,51; IC95%=1,11-5,68) foram as que tiveram mais chance de ter um pré-natal adequado. Observou-se que a assistência pré-natal não atendeu ao que é preconizado, como a idade gestacional de início do pré-natal, número mínimo de consultas a serem feitas, realização de alguns exames (hemograma, glicemia, tipagem sanguínea e fator Rh) e oferta de orientações sobre sinais de risco e de parto. Quanto à satisfação com a assistência pré-natal recebida, mais da metade das mulheres mostrou-se insatisfeita com o tempo de espera para ser atendida pela profissional de saúde. Conclusão: De modo geral, os critérios preconizados para que uma assistência ao pré-natal seja de alta qualidade não estão incorporados na prática clínica no município de Nampula.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health - maternal and child / saúde - materno-infantil; health / saúde

Gender and countering violent extremism (CVE) in the Kenya- Mozambique region - Idris, Iffat (Institute of Development Studies, 2020)
This evidence synthesis drew on a mixture of academic and grey literature. While the literature on Kenyan women and Al-Shabaab was quite extensive (albeit with gaps, e.g. on returnees), nothing was found on women and Ansar al-Sunnah/violent extremist groups operating in northeastern Mozambique and the Mozambique-Tanzania cross-border region. This report should be read in conjunction with two earlier reviews of gender and CVE (Idris & Abdelaziz, 2017; Idris, 2019). This report builds on those – focusing on the literature on gender and CVE published since then, and on recent guidance on CVE programming – rather than reproducing their findings. This report covers three main themes: the role of women in violent extremism and in CVE (drawing on global evidence); Kenyan women’s involvement in Al-Shabaab and approaches to CVE and gender in that country; and recommendations/guidance for gender and CVE programming.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

The Relationship Between Population Growth, Age Structure, Conflict, and Governance in Sub- Saharan Africa - O’Driscoll, Dylan (Institute of Development Studies, Brighton, UK, 2020)
This report addresses the relationship between population growth, age structure, and conflict in Sub-Saharan Africa (SSA). The literature reviewed for this report presents strong evidence that age structure and population growth matter for conflict. There is particularly strong evidence that points to the relationship between young age structure and conflict, although studies that disaggregate types of conflict and characteristics of young age structures (urban, male, etc.) tend to offer more robust findings. Youth bulges in particular have been associated with increased risk of conflict. The general consensus is that, in countries that will continue to experience high rates of population growth and large youth cohorts, the potential for conflict will continue to be elevated. COVID-19 is putting a dent in already weak formal employment and education. Policy responses to the pandemic will have lasting impacts for those most affected, including young people, and should therefore include them in response. The following policy recommendations are made in the literature including Patriarchal gender norms and masculinity contribute to violence and conflict, and thus policies aimed at increasing gender equality help mitigate conflict risk; The prediction that youth bulge is associated with the onset of conflict should encourage policymakers in countries with young age structures to address societal and economic inequality and foster greater inclusion of the younger cohorts into society; and Youth underemployment (and unemployment) remain an issue in SSA; bringing about structural changes that facilitate the transition into the labor market is likely to mitigate the conflict risks associated with youth bulges
Accepted: 2020-11-04T11:13:17Z Publisher: Institute of Development Studies
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; conflict / conflito; gender / género; youth / juventude

Do male engagement and couples’ communication influence maternal health care-seeking? Findings from a household survey in Mozambique - Sitefane, Gilda G.; Banerjee, Joya; Mohan, Diwakar; Lee, Connie S.; Ricca, Jim; Betron, Myra L.; Cuco, Rosa Marlene Manjate (BMC Pregnancy and Childbirth, 2020)
This study explored effects of couples’ communication and male participation in birth preparedness and complication readiness (BPCR) on delivery in a health facility (“institutional delivery”). A cross-sectional, baseline household survey was conducted in November 2016 prior to an integrated maternal and child health project in Nampula and Sofala Provinces in Mozambique.
Keywords: G - Mozambique / Moçambique; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

O Trabalho Doméstico Em Moçambique: Uma Década após a Formalização - Castel-Branco, Carlos Nuno (Desafios para Moçambique 2020, 2020)
O estudo verifica que houve alguns avanços na última década, incluindo: a definição de um quadro regulamentar para o trabalho doméstico, a proliferação de organizações de trabalhadores domésticos filiadas ao movimento sindical e uma maior valorização por parte da sociedade (e dos empregadores) deste sector. No entanto, existem vários desafios, entre os quais: um quadro regulamentar fraco e fracamente implementado; a dificuldade de mobilização colectiva num sector íntimo, disperso, e ultra-explorado; um baixo nível de colaboração entre organizações de trabalhadores domésticos e a marginalização de organizações no contexto de um movimento sindical machista e de um movimento feminista classista. O estudo identifica algumas oportunidades, incluindo a ratificação da Convenção 189, a revisão de Lei de Trabalho, que pode criar uma abertura para reforçar o quadro regulamentar, e o reforço das organizações de trabalhadores domésticos e de colaborações estratégicas entre o movimento sindical e o movimento feminista. Porém, o estudo também identifica algumas ameaças, como a crise económica e financeira, que aumentou o custo de vida e aprofundou uma política de austeridade, a falta de vontade política por parte do Estado e a concorrência entre as organizações da sociedade civil. Com base nesta análise, o estudo apresenta as seguintes recomendações para o Estado e para o movimento sindical e feminista.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; employment / emprego; gender / género

Trabalho em Função do Género, Trabalho Migratório: Reformar os Regimos do Açúcar em Xinavane, Moçambique - Lazzarini, Alicia Hayashi (Desafios para Moçambique 2020, 2020)
O açúcar tem desempenhado um papel fundamental e controverso em Moçambique. Desde 1996, o Governo moçambicano e a iniciativa privada aproveitaram-se da ideia de que a África é a «última fronteira» do investimento (Diop et al., 2015; The Economist, 2013; Sizemore, 2012) para reinvestir numa economia devastada pela guerra civil e «reabilitá-la». Com um crescimento de sete por cento e, nos últimos anos, uma das taxas mais elevadas de investimento estrangeiro em África, Moçambique tem sido apresentado como um país posicionado para um crescimento explosivo. O açúcar tem desempenhado um papel crucial na transformação do presumível potencial da paisagem moçambicana em produtividade e na restauração da capacidade da nação para competir em mercados globais. A Açucareira de Xinavane tem sido o exemplo notável deste esforço de reabilitação. Antigamente conhecido como uma propriedade colonial menor, o actual empreendimento conjunto entre o Governo de Moçambique e a empresa sul-africana Tongaat Hulett tornou a Açucareira a maior plantação de açúcar do País. Entre 2005 e 2013, a área de cana-de-açúcar cultivada triplicou de 6000 para mais de 17 000 hectares (ha), com um aumento correspondente na produção de cana-de-açúcar, de 500 000 para 1,5 milhões de toneladas. A nova abordagem da produção de Xinavane enfatiza as técnicas de quantificação, cálculo e gestão originárias dos institutos de pesquisa de açúcar da África do Sul. Representantes da empresa e da indústria nacional descrevem a reabilitação da fábrica como a implementação directa da prática industrial padrão, apesar de enfrentar um contexto de «desenvolvimento» desafiador. Nas descrições do Governo e da indústria, o açúcar fornecerá empregos, infra- -estruturas necessárias e centros rurais com bancos, escolas e hospitais que beneficiarão todos os moçambicanos. Com este objectivo, foram levados a Xinavane peritos industriais regionais para formar gestores moçambicanos, supervisionar o restabelecimento e o crescimento da indústria e, finalmente, tornar possível o «progresso» económico e social de um país emergente de uma situação de conflito e, assim, construir uma economia capitalista competitiva. O presente artigo levanta questões sobre as tensões no seio desta abordagem tecnicamente estruturada. Analisa sobretudo as estratégias emergentes de gestão do trabalho, e identifica a forma como as «novas» práticas gerem uma força de trabalho grande e anteriormente indisciplinada. Esta gestão tem sido realizada através da divisão geográfica e de género, que não só reforça as baixas valorizações sociais e materiais da vida e do trabalho rural moçambicano, mas também restabelece um regime de trabalho profundamente associado à violência do passado colonial. Ao interrogar a dinâmica material e discursiva da «ciência da indústria» e da «tecnologia» na prática, ponho em causa os alegados impactos modernizadores desta abordagem «nova» no Moçambique pós-colonial.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; employment / emprego; gender / género

Redressing the gender imbalance: a qualitative analysis of recruitment and retention in Mozambique’s community health workforce - Steege, Rosalind; Taegtmeyer, Miriam; Ndima, Sozinho; Give, Celso; Sidat, Mohsin; Ferrão, Clara; Theobald, Sally (Human Resources for Health, 2020)
Findings: In-depth interviews (n = 30), key informant interviews (n = 1) and focus group discussions (n = 3) captured experiences and perceptions of employment processes. Intra-household decision-making structures mean women may experience additional barriers to join the APE programme, often requiring their husband’s consent. Training programmes outside of the community were viewed positively as an opportunity to build a cohort. However, women reported difficulty leaving family responsibilities behind, and men reported challenges in providing for their families during training as other income-generating opportunities were not available to them. These dynamics were particularly acute in the case of single mothers, serving both a provider and primary carer role. Differences in attrition by gender were reported: women are likely to leave the programme when they marry, whereas men tend to leave when offered another job with a higher salary. Age and geographic location were also important intersecting factors: younger male and female APEs seek employment opportunities in neighbouring South Africa, whereas older APEs are more content to remain. Conclusion: Gender norms, roles and power dynamics intersect with other axes of inequity such as marital status, age and geographic location to impact recruitment and retention of APEs in Maputo Province, Mozambique. Responsive policies to support gender equity within APE recruitment processes are required to support and retain a gender-equitable APE cadre.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Mozambique Annual Report 2020: Responding to a Year of Crisis - Wojnar, Andrea M; Lomelin, Jessica; Baker, Daniel; Salu, Karlina; Macangira, Assane; Manjate, Epidauro (UNFPA, 2020)
In the case of Mozambique, the pandemic came on the heels of two destructive cyclones that had devastated large parts of the country in 2019 and whose consequences were still being felt. In northern Mozambique, increasing violence in Cabo Delgado province resulted in a surge of internally displaced persons into local communities in Cabo Delgado, Nampula and Niassa provinces. With host communities ill equipped to meet the needs of those displaced, this population movement created a new humanitarian crisis in the midst of the pandemic. Like all of our governmental, civil society and donor partners, the resilience of UNFPA was tested, and we had to adjust quickly after the first case of COVID-19 was confirmed in March and the Government declared a state of emergency. At the most basic level, women continued to get pregnant and babies were still being born, even in the middle of a pandemic. Addressing the needs of adolescent girls and young women could not be put on hold. Helping to meet the needs of the symbolic target of UNFPA’s work – “the 10-year-old girl” – could not wait until she was 11. Helping to meet her aspirations for the future, advocating and working for her growth and self-fulfillment as a woman leading a healthy, productive and violence-free life – these could not wait a year.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; youth / juventude

Prevalence of institutional delivery and its correlates amongst women of reproductive age in Mozambique: a cross-sectional analysis - Yaya, Sanni; Idriss-Wheeler, Dina; Shibre, Gebretsadik; Amouzou, Agbessi; Bishwajit, Ghose (Reproductive Health, 2020)
The healthcare system in Mozambique is striving to reduce the high maternal and child mortality rates and stay on par with the Sustainable Development Goals (SDG 3.1). A key strategy to curb maternal and child mortality is to promote the use of professional childbirth services proven to be highly effective in averting maternal deaths. Currently, little is known about the use of childbirth services in Mozambique. The present study investigated the prevalence of professional healthcare delivery services and identified their sociodemographic correlates.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde